Legitimacy of unseen actors in international adjudication - Baetens, Freya (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2019)
"'Unseen actors' are vital to the functioning of international courts and tribunals, exercising varying levels of influence on the adjudicatory process and its outcome. The last few decades have witnessed an expansion in the number of international judicial bodies. Although these bodies differ in their institutional make-up and functions, a characteristic shared among them is their reliance on the contribution of individuals or entities other than the judicial decision-makers themselves. Unseen actors may take the form of registries, secretariats, law clerks and legal officers, but they also include non-lawyers such as translators, members of the medical profession and scientific experts. Some of these actors may be 'more unseen' than others but most remain nameless in the written decisions, and the extent of their contribution is generally unclear. The opaqueness of their role, combined with the significance of the judicial decision for the parties involved as well as for a wider range of stakeholders, raises questions about the impact of these unseen actors on the legitimacy of international adjudication as such. For example, an unseen actor's influence has formed a ground upon which an arbitral award was challenged, as substantial parts had allegedly been written by a legal assistant rather than the arbitrators themselves. The domestic court adjudicating the dispute in first instance set aside the award on a different ground, so it did not address this point; the case is currently pending on appeal. This book aims to answer such legitimacy questions and identify 'best practices', where feasible, through a multifaceted enquiry into possible common connections and patterns in the institutional makeup and daily practice of international courts and tribunals"--
Institutional perspectives -- Nomination and appointment -- Case management and deference to the bench -- Confidentiality and transparency -- Ethics and accountability -- External influences and activities
Includes bibliographical references and index.
Keywords: Arbitration (International law); Jurisdiction (International law); International courts; Law / International; Arbitration (International law); International courts; Jurisdiction (International law); International courts; International arbitration; Legitimacy